Wasser in Attersee : Gemälde, Graphik, Photographie. - Baum, Peter (Linz : Lentos Kunstmuseum Linz, 2003)
Adlmannseder, Reinhard ; Aigner, Rolf ; Alechinsky, Pierre ; Anzinger, Siegfried ; Attersee, Christian Ludwig ; Barfuss, Ina ; Braun, Theo ; Brehm, Dietmar ; Eberl, Irma ; Errò ; Gertsch, Franz ; Hofkunst, Alfred ; Klimo, Karoly ; Knogler, Gerhard ; Kowarik, Ingrid ; Lassnig, Maria ; Matsukawa, Takako ; Mauracher, Michael ; Merwart, Ludwig ; Molles, Andrew ; Noël, Georges ; Plessi, Fabrizio ; Radak, Eszter ; Scheibl, Hubert ; Scheidl, Roman ; Schrödl, Werner ; Schuster, Robert ; Sengl, Peter ; Steffner, Christoph ; Stifter, Wolfgang ; Szücs, Attila ; Tezak, Edgar ; Thuma, Gerlinde ; Trumler, Gerhard ; Wanke, Johannes ; Wesselmann, Tom ; Zaborszky, Gabor ; Zens, Herwig
Duits
Exhibition. Wasser in Attersee. Atterseehalle in Attersee. Lentos Kunstmuseum Linz. 12.07.2003 - 24.08.2003.
boek